Importancia del uso de fertilizantes orgánicos e inorgánicos en el rendimiento y calidad del fruto jackfruit (Artocarpus heterophyllus). - Vásconez Montiel, Génesis Cristina (2025)
This project analyzes the importance of the use of organic and inorganic fertilizers in the cultivation of jackfruit (Artocarpus heterophyllus), a highly nutritious tropical fruit of growing relevance in international markets. The research is carried out in the province of Los Ríos, Ecuador, where this crop shows growing commercial potential. A literature review methodology was used, collecting information on the advantages and disadvantages of each type of fertilization. Organic fertilizers, such as compost and manure, improve soil structure, promote biodiversity and raise the nutritional quality of the fruit; However, its availability is limited and its effect is slower. In contrast, inorganic fertilizers, such as urea and phosphates, increase productivity in the short term, but their excessive use can cause soil degradation and water pollution. The results suggest that a balanced combination of both fertilizers represents the best strategy to maximize production without compromising environmental sustainability. It is concluded that it is essential to promote local research and training programs that allow farmers to adopt optimal fertilization practices. Likewise, the importance of jackfruit cultivation is highlighted as a viable alternative to diversify agricultural production in Ecuador, strengthening food security and promoting a sustainable development approach in agriculture.